Spherical submicron YAG:Ce particles with controllable particle outer diameters and crystallite sizes and their photoluminescence properties. Issue 48 (10th September 2021) - Dani Nandiyanto, Asep Bayu; Kito, Yusuke; Hirano, Tomoyuki; Ragadhita, Risti; Le, Phong Hoai; Ogi, Takashi
Abstract : We demonstrate the synthesis of spherical submicron YAG:Ce particles with controllable particle outer diameters and crystallite sizes and their photoluminescence properties, produced by a flame-assisted spray-pyrolysis method with annealing process. Abstract : The purpose of this study was to demonstrate the preparation of spherical submicron YAG:Ce particles with controllable particle outer diameters and crystallite sizes and their photoluminescence (PL) properties, which were produced using a flame-assisted spray-pyrolysis method followed by the annealing process. The correlation of particle outer diameter, crystallite size, and PL performance of the prepared particles was also investigated. Experimental results showed that the increases in the particle outer diameters have an impact on the obtainment of higher PL performance. Large particle outer diameters permitted the crystallites to grow more, whereas this is in contrast to the condition for small particle outer diameter having limitations in crystallite growth. This study also found that too large outer diameter (>557 nm) was not effective since crystallites cannot grow anymore and it permits possible scattering problems. This study provides significant information for optimizing synthesis parameters for controlling particle outer diameters and crystallite sizes, which could be relevant to other functional properties, especially for lens, solar cell, and LED applications.